DEVELOPMENT OF TEA LOCAL COMPANY THROUGH BLUE OCEAN STRATEGY - Akbar Daffa Raharja; Roaida Yanti; Qurtubi; Rahma Fariza (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2021)
By the development and ease of today's technology line, it is necessary to design a new marketing strategy to find out the position of EFAS and IFAS, as well as find the right marketing strategy proposal for the company using the Blue Ocean Strategy method. This strategy method offers a concept for companies looking for new areas that have not been entered by competitors. The purpose of this study is to find out and explain the external and internal environment through SWOT analysis, how to apply the Blue Ocean Strategy in increasing sales, and excel in compete so that it can be applied to the smooth running of the business in the future. Based on the results of a study involving 52 respondents, it is known that the company's position is in quadrant III with a value on the X axis of -0.1 and the Y Axis of 0.2, meaning that there is a need for a change in strategy with the opening of existing opportunities. Furthermore, the proposed four-step performance framework, the variables that must be leveled are product quality, advertising, the appearance of the company, the ease of finding products, and promotion, and the variable factors created are the renewal of the company's image (re-branding), and the addition of a narrative to the product menu.